The Mediating Role of Resilience and Extraversion on Psychological Distress and Loneliness Among the General Population of Tyrol, Austria Between the First and the Second Wave of the COVID-19 Pandemic - Chernova, Anna; Frajo-Apor, Beatrice; Pardeller, Silvia; Tutzer, Franziska; Plattner, Barbara; Haring, Christian; Holzner, Bernhard; Kemmler, Georg; Marksteiner, Josef; Miller, Carl; Schmidt, Martin; Sperner-Unterweger, Barbara; et al. (Frontiers in Psychiatry, 2021)
Background: During the first three weeks of the COVID-19 pandemic, the federal state of Tyrol, Austria had one of the strictest curfews in Austria and worldwide. The aim of the current study was to investigate the assumingly protective role of resilience and extraversion and its impact on mental health following such an uncertain and unpredictable situation. Methods: Between the first and the second wave of the pandemic, adult residents of Tyrol were invited to participate in an online survey. Next to the assessment of sociodemographic and COVID-19-related variables the Brief-Symptom-Checklist, the Three-Item Loneliness Scale, the Resilience Scaled, and the Big Five Inventory were used to assess psychological distress, loneliness, resilience, and extraversion. Mediation analysis was used to investigate the role of resilience and extraversion in the context of age-, sex-, and partnership- related differences in psychological distress and loneliness. Results: 1,045 participants took part in the survey (68.2% female). Overall, psychological distress and severe loneliness were more often detected in women and singles. They also were less resilient, while men and singles presented with a lower degree of extraversion. Study participants under the age of 30 experienced severe loneliness more frequently than older people, whereas psychological distress, resilience, and extraversion were comparable between age groups. Resilience significantly mediated the relationship between both study participants’ sex and partnership situation on one hand and psychological distress and severe loneliness on the other. In Addition extraversion significantly mediated the relationship between participants’ partnership situation and psychological distress. Discussion: Our findings suggest that women, singles, and young people may be particularly affected by the measures and sequelae of the COVID-19 pandemic. Interventions promoting resilience and extraversion among these groups are urgently needed to foster mental health. Ideally, they can be utilized at home in case of renewed mobility restrictions or quarantine in the future.